Customers Awareness and Purchase Behaviour towards Organic Food - Abas, Siti Aisah; Ishak, Lily Nurainul Ashikin; Othman, Mohd Amar Ridham; Mohd Fuza, Zatul Iffah (MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2021)
Organic food may be a safer and healthier alternative to conventional food, particularly in COVID19 pandemic conditions where stay-at-home arrangements may encourage the willingness to plan, select, and prepare more nutritious foods in order to strengthen the immune system or maintain fitness. However, organic food consumption is relatively still low even in countries with a well-established organic food market. A similar pattern is happening in Malaysia, where there is an increase in organic farms throughout the years, yet the consumption level is very disappointing. Therefore, this study is conducted to explore customers awareness and purchase behaviour among Malaysian customers. A questionnaire survey is used to collect data from the members of consumer association. Data from 403 respondents are collected, analysed and discussed in the study. This study found out that most Malaysian food buyers are aware of organic food and buy organic food. Most food buyers understand organic food as natural food. The key reason for buying organic food is health-related. In comparison, the main reason for not buying organic food is the price itself. This study will contribute to the body of knowledge regarding Malaysian organic food consumers. The findings of this study can be utilised to understand the Malaysian organic food market better and, simultaneously, lead to the development of the organic food market and the organic food consumption level in Malaysia.